Upaya Mengembangkan Kurikulum Madrasah Ibtidaiyah Di Era Globalisasi - Laesti Nurishlah; Siti Nursholihah; Anisa Nurlaila; Hana Rizki Farhana; Khaeroni (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
In the era of globalization, educational institutions such as Madrasah Ibtidaiyah are faced with the challenge of maintaining Islamic and traditional values. This qualitative research investigates Madrasah Ibtidaiyah's efforts to face globalization by strengthening the integration of Islamic values in the curriculum, promoting local culture, community participation, and teacher training. With a balanced approach between global and local values, Madrasah Ibtidaiyah has the potential to maintain the integrity of students' Islamic identity and traditional culture. These strategic steps aim to prepare students to face global challenges while adhering to the values they profess. Through the development of forward-looking strategies, it is hoped that Madrasah Ibtidaiyah can become an effective agent in promoting education rooted in Islamic values and strengthening social cohesion amidst global dynamics.